Evaluating the taxonomic identity of two species of papaya relatives: Vasconcellea lanceolata and Vasconcellea quercifolia (Caricaceae) - Iraola-Linares, Valeria; Roque, José; Evangelista-Vargas, Diego; Cano, Asunción; Carvalho, Fernanda Antunes (Phytotaxa, 2025)
Vasconcellea is widely distributed throughout the Neotropical region, particularly in the Andes, where it occurs in Argentina, Bolivia, Brazil, Colombia, Ecuador, Paraguay, Peru, and Uruguay. In this study, the taxonomic identity of Vasconcellea quercifolia A.St.-Hil., the type species of the genus, was evaluated. A total of 296 herbarium specimens were examined, and morphometric analyses were conducted to determine whether V. lanceolata A.DC. should continue to be considered a heterotypic synonym. Significant morphological variation and distinct geographic distribution patterns were identified, supporting the recognition of both species. As a result, the number of species within Caricaceae increases to 40 and Vasconcellea to 27. Morphological descriptions, distribution maps, and an identification key for both species are provided, together with a discussion of the cultural significance of “pati,” the local name for V. lanceolata, which was an important plant for the pre-Hispanic Wari culture in Peru.